The Effect of Teaching Style Variations on Student’s Learning Achievement at Sasmita Jaya Vocational School, South Tangerang - Dewi Sartika; Sam Cay; Ali Zaenal Abidin (universitas Pamulang, 2021)
The goal to be achieved in this study is to determine the effect of teacher teaching style on student achievement at SMK Sasmita Jaya, South Tangerang. The time of the research takes place from December 2020 to April 2021. In improving education, of course, it is influenced by teaching and learning interactions during the learning process. The intended interaction is a reciprocal relationship between teachers and students in the teaching and learning process. This research method is an associative research using a quantitative approach. The subjects of this study were 75 students of class XI majoring in Marketing at SMK Sasmita Jaya, South Tangerang. While the sample used was 75 respondents using the saturated sample technique. Collecting data using interviews, questionnaires, documentation, and literature study. While the data analysis using Validity Test, Reliability Test, Simple Linear Regression, Correlation Coefficient, Coefficient of Determination and Significance Test. The results in this study indicate that the value of Y=16.948+0.550x. The results of the calculation of the correlation coefficient indicate that there are not examined in this study. From the results of the significant test calculation, it is known (4.282 > 1.993) then H0 is rejected and H1 is accepted, thus it is evident that there is a significant influence between teacher teaching styles on student achievement at SMK Sasmita Jaya, South Tangerang.